Old kingdom copper tools and model tools - Odler, Martin (Archaeopress Egyptology, 2016)
This volume gathers the textual, iconographic and palaeographic evidence and examines artefacts in order to revise the common view on the use of copper alloy tools and model tools in the Old Kingdom